2014
DOI: 10.1103/physreva.89.051605
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic optical superlattices with topological bands

Abstract: We introduce an all-optical approach to producing high-flux synthetic magnetic fields for neutral atoms or molecules by designing intrinsically time-periodic optical superlattices. A single laser source, modulated to generate two frequencies, suffices to create dynamic interference patterns which have topological Floquet energy bands. We propose a simple laser setup that realizes a tightbinding model with uniform flux and well-separated Chern bands. Our method relies only on the particles' scalar polarizabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 50 publications
0
69
0
Order By: Relevance
“…In the Abelian case, fractional quantum Hall (FQH) physics could be realized. To generate and stabilize such FQH liquids, it is crucial to develop schemes leading to topological flat bands [103,178,375], namely, dispersionless bands characterized by non-zero Chern numbers, which are well separated with respect to higher energy bands [see Fig. 26 for such a configuration offered by the Hofstadter model at flux Φ = 1 /5].…”
Section: Discussionmentioning
confidence: 99%
“…In the Abelian case, fractional quantum Hall (FQH) physics could be realized. To generate and stabilize such FQH liquids, it is crucial to develop schemes leading to topological flat bands [103,178,375], namely, dispersionless bands characterized by non-zero Chern numbers, which are well separated with respect to higher energy bands [see Fig. 26 for such a configuration offered by the Hofstadter model at flux Φ = 1 /5].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, it has been shown that periodic perturbations can be used as a flexible experimental knob to realize new phases not accessible in equilibrium systems [34][35][36][37], synthetic (engineered) matter [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54], and quantum motors, which are similar to a quantum ratchet [55,56]. This new line of research, which can be termed 'Floquet engineering', has motivated a renaissance of interest in periodically driven systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, extensions of the moving-secondary-lattice and the asymmetric shaking schemes have been proposed for the creation of Haldane-type hexagonal-lattice Chern insulators, nonabelian gauge fields (spin-orbit coupling) and topological (spin-Hall) insulators, as well as Weyl semi-metals (Baur et al, 2014;Bermudez et al, 2012;Dubček et al, 2014;Kennedy et al, 2013;Struck et al, 2012). Another approach for Floquet engineering of artificial magnetic fields or spin-orbit coupling is to construct driving protocols given by a sequence of pulses during which different external fields are present (Goldman and Dalibard, 2014).…”
Section: Further Possibilitiesmentioning
confidence: 99%